Effect of salinity on the egg hatching and early larvae of horseshoe crab Tachypleus gigas (muller, 1785) in laboratory culture - Kasim, Zaleha; Izyan, Hazwani; H., Siti Hamidah; Yunus, Kamaruzzaman; Khan Chowdhury, Ahmed Jalal (Asian Network for Scientific Information, 2011)
Tachypleus gigas (Muller) the Southeast Asian horseshoe crab, is found to nest on sandy beaches in Malaysia, thus biological information about survival of this living fossil become crucial. Laboratory experiments were carried out to investigate the effect of salinity on duration to maturation and hatching success of their eggs. The effect on size, morphological changes and growth of the hatched larvae was also investigated. Eggs of T. gigas were collected from the newly nests made on breeding beach of Pekan, Pahang (Lat 3° 56.915’N; Long 103°21.933’ E) in Peninsular Malaysia. Triplicates of five different salinities (15, 20, 25, 30 and 35 ppt) were chosen for the experiments. A vernier caliper was used for size measurement under a stereo microscope. The morphological changes in prosomal width and length, body length, telson length, opisthosoma length and total length were recorded. Salinity range of between 25 and 35 ppt could be an optimal incubation condition. No egg hatched at salinity 15 and 20 ppt. Highest percentage of hatching was found at 30 ppt (91.11±5.57%). Hatching also occurred at 25 and 35 ppt with 65.56±1.73% and 74.4±2.31% success rate, respectively. The shortest molting time occurred at 15 ppt (25 days after hatching). Total size changes in larvae were also highest at 15 ppt but lowest at 35 ppt. There was no mortality in larvae maintained in all treatments. Early larval development would also affected by the salinity stress but its seemed tolerable.